2018
DOI: 10.2147/prbm.s177457
|View full text |Cite
|
Sign up to set email alerts
|

Accurate empathy of romantic partners increases pain ratings but promotes recovery

Abstract: BackgroundPerceived empathy is a commonly used strategy to cope with pain and is crucial for maintaining intimacy in dyadic relationships.Materials and methodsThis study used the cold pressor test to investigate how perceived empathy and relationship type interact with the subjective perception of pain and objective measures of recovery time, using heart rate as an index. One hundred and ninety participants were recruited, including 49 friend dyads and 46 romantic partner dyads. Perceived empathy was manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Perceived empathy is the degree to which individuals perceive others to empathize with them. To our knowledge, a single Chinese experimental study involving 194 participants demonstrated that accurately perceiving empathy from a romantic partner more effectively alleviates individual social pain and reduces individual recovery time than does perceiving empathy from a friend [19]. Despite its acknowledged importance, the influence of different dimensions of perceived spousal empathy-emotional, cognitive, and behavioural empathy-on HRQoL among pregnant women is presently unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Perceived empathy is the degree to which individuals perceive others to empathize with them. To our knowledge, a single Chinese experimental study involving 194 participants demonstrated that accurately perceiving empathy from a romantic partner more effectively alleviates individual social pain and reduces individual recovery time than does perceiving empathy from a friend [19]. Despite its acknowledged importance, the influence of different dimensions of perceived spousal empathy-emotional, cognitive, and behavioural empathy-on HRQoL among pregnant women is presently unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Natalie's study showed that in the parents of newborn babies, the couples with high levels of empathy also had high levels of sexual and relationship satisfaction (Rosen et al, 2017). According to the result of the study of Sun et al (2018) study on how empathy and relationship type interact with pain, the pain test survey showed that romantic partners recovered faster than friends, and empathy may modulate psychological and physiological responses in romantic relationships (Sun et al, 2018). The results of Lingdan's study also verified that empathy can lead to the enhancement of earlier posterity negativity (EPN) and late positive potential (LPP) components in brain processing signals due to pain signals received by partners; this explains the possible role of empathy in dealing with stress stimuli in marital relationships from the perspective of neurotic electrophysiology (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Natalie's study found that in the parents of newborn babies, the couples with high levels of empathy also had high levels of sexual and relationship satisfaction [24]. According to the result of the study of Sun et al [25] study on how empathy and relationship type interact with pain, the pain test survey showed that romantic partners recovered faster than friends, and empathy may modulate psychological and physiological responses in romantic relationships [25]. The results of Lingdan's study also verified that empathy can lead to the enhancement of earlier posterity negativity (EPN) and late positive potential (LPP) components in brain processing signals due to pain signals received by partners; this explains the possible role of empathy in dealing with stress stimuli in marital relationships from the perspective of neurotic electrophysiology [26].…”
Section: Introductionmentioning
confidence: 99%